Environmental Law Handbook by Thomas F.P. Sullivan (Editor) - Ann Jensen (Issues in Science and Technology Librarianship, 1997)
This article reviews the book Environmental Law Handbook, 14th edition. Rockville, MD:  Government Institute, Inc.,  1997, by Thomas F.P. Sullivan, Editor.